Prosthetic rehabilitation of a microtia patient by adhesive retained auricular prosthesis: A dental technique. - Nizami, Md Minhaz Ul Islam; Rahman, Ahmed Mushfiqur; Jamayet, Nafij Bin; Alam, Mohammad Khursheed; Ghani, Zuryati Ab; Husein, Adam (Bangladesh Journal of Medical Science, 2019)
Introduction: Auricular deformity can be emotionally traumatising and affects social behavior of an individual. In such cases, aesthetically acceptable prosthesis serves as a viable alternative technique to surgical reconstruction. Case description: Impression of the auricular defect was taken by light and regular body of poly vinyl siloxane impression material. Wax sculpting was challenging due to the bulgy remnant of the defected ear. The wax pattern was made very thin to accommodate and mask the remnant without compromising the aesthetic. Trial on the patientwas done for correction of the contours, angulation, height and width according to the normal contralateral ear. The intrinsic coloration of a Room Temperature Vulcanizing silicone was done and poured in a custom-made three-piece mold. Before the final issue of the auricular prosthesis, extrinsic coloration was done based on the surrounding area of the defect. Discussion: Fabrication of adhesive retained prosthesis is challenging in patients with large deformed soft tissue who refuse to undergo surgical repair. A modified wax sculpting was done to overcome this challenge. Medical grade silicone was the choice of material because of its flexibility, biocompatibility and life like appearance. Conclusion: Replacement of missing ear is a difficult and multi-step task in which extensive array of materials and techniques need to be employed. This fabrication technique is alternative to surgical repair with the utilization of available and economical materials. Bangladesh Journal of Medical Science Vol.18(2) 2019 p.437-439